Conformational analysis of N, N, N‐Trimethyl‐(3, 3‐dimethylbutyl)ammonium iodide by NMR spectroscopy: a sterically hindered trans‐standard. (23rd September 2013) - Liu, Albert Tianxiang; Nag, Mrinmoy; Carroll, William R.; Roberts, John D.
Abstract : A predominantly trans ‐1, 2‐disubstituted ethane system – N, N, N ‐trimethyl‐(3, 3‐dimethylbutyl)ammonium iodide – is of particular interest for conformational analysis, because it contains both an organic and a highly polar substituent, making it soluble and thus applicable to study in a large variety of solvents. The fraction of the trans conformer of this molecule in a wide range of protic and aprotic solvents was determined by the nuclear magnetic resonance proton couplings to be approximately 90%, in contrast to the previously assumed 100%. The consistently strong preference of the trans conformation should establish N, N, N ‐trimethyl‐(3, 3‐dimethylbutyl)ammonium iodide as a possibly useful ' trans ‐standard' in conformational analysis, much more so than 1, 2‐ditert‐butylethane, which has a poor solubility in many solvents. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : A predominantly trans ‐1, 2‐disubstituted ethane system – N, N, N ‐trimethyl‐(3, 3‐dimethylbutyl)ammonium iodide – is of particular interest for conformational analysis, because it is soluble and thus applicable to study in a large variety of solvents. The fraction of the trans conformer of this molecule in a wide range of protic and aprotic solvents was determined by the nuclear magnetic resonance proton couplings to be approximately 90%, in contrast to the previously assumed 100%. The consistently strong preference of the trans conformation should establish N, N, N ‐trimethyl‐(3, 3‐dimethylbutyl)ammonium iodide as a possibly useful ' trans ‐standard' in conformational analysis.